Proposed local art criticism’s model for traditional ceramic :mambong pottery as case study. - Iwan Zahar (2014)
Malaysia have various crafts include crafts for religious purpose, however, we are still using Feldman’s art criticism model. Feldman’s criticism model do not accommodate contextual value of the crafts and is not made to judge crafts. Most of art lecturers are familiar with Feldman’s art criticism model because its simplicity which only four phases; describe, analyze, interpret, and judge. This study used content analysis and interviewed two postgraduate students who studied pottery in Mambong Village. I modify Feldman’s art criticism model and propose three phase model; internal, original and historical context. Internal context; description include visual and material descriptions, how pottery or handicraft is made, original context; styles, values, principle design within local context, compare and contrast, examine original and other country influences the styles and historical context: historical moments, events, and trends relate to handicraft, how other interpreters have understood it, where it has been placed in the history of art. The model will help student or researchers to evaluate and appreciate the value of crafts including religious crafts. Students will not only know how to judge the quality of the crafts, but they will also appreciate the history and cultural context of the crafts.